The relationship between running load, strength, muscle architecture and hamstring strain injury across two seasons of elite male Australian football: a prospective cohort study - Breed, R.; Opar, D. A.; Johnston, R. D.; Hickey, J. T.; Williams, M. D.; Maniar, N.; Timmins, R. G. (Sports Medicine - Open, 2025)
Background Previous research has demonstrated a relationship between modifiable (e.g. hamstring strength, muscle fascicle length and high-speed running load), non-modifiable factors (e.g. age, previous injury) and hamstring strain injury (HSI) risk. However, these factors have mostly been assessed in isolation and no study to date has investigated the associations between running load, strength and muscle architecture with HSI risk. The study aim was to explore the interactions between modifiable HSI risk factors that are commonly assessed within elite Australian footballers.